(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article investigates the phenomenon of virtual communication, defines its main characteristics and difference from real communication. The works of scientists, their conclusions on the impact of virtual communication are analyzed. The attitude of modern youth to virtual communication is clarified. There was determined the influence of virtual communication on the development of communication skills of adolescents and teenagers. The results of research on this problem are presented. Conclusions are made on the basis of the analyzed literature and the conducted research, which testify to the possibility of positive and negative influence of virtual communication on the development of personal communication processes.